2008
DOI: 10.1021/jp804240a
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Studies on Mobility of the Glycosidic Linkage in Seven Disaccharides

Abstract: Isobaric dielectric relaxation measurements were performed on seven chosen disaccharides. For five of them, i.e., sucrose, maltose, trehalose, lactulose, and leucrose, we were able to observe the temperature evolution of the structural relaxation process. In the case of the other disaccharides studied (lactose and cellobiose), it was impossible to obtain such information because of the large contribution of the dc conductivity and polarization of the capacitor plates to the imaginary and real part of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
94
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 64 publications
16
94
0
Order By: Relevance
“…Four relaxation processes were identified in dielectric spectra of both the saccharides. The slower one was identified as a structural relaxation process; the next one, not observed by the others, was assigned as Johari-Goldstein (JG) β-relaxation, while the last two secondary modes were of the same nature as found by Kaminski et al 2 Kwon et al 1 demonstrated that both in trehalose and maltose it is possible to follow dynamics of structural relaxation process even in the vicinity of the glass transition temperature. From the dielectric loss spectra presented in Figs.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Four relaxation processes were identified in dielectric spectra of both the saccharides. The slower one was identified as a structural relaxation process; the next one, not observed by the others, was assigned as Johari-Goldstein (JG) β-relaxation, while the last two secondary modes were of the same nature as found by Kaminski et al 2 Kwon et al 1 demonstrated that both in trehalose and maltose it is possible to follow dynamics of structural relaxation process even in the vicinity of the glass transition temperature. From the dielectric loss spectra presented in Figs.…”
mentioning
confidence: 79%
“…At this place, it should be also explained why this process was visible in loss spectra of trehalose and maltose shown by Kwon et al, 1 while it is absent in dielectric spectra reported by Kaminski et al 2 and De Gusseme et al 4 To address this question, we would like to refer the readers to papers by Paluch et al 7 and Richert 9, 10 who showed that the Debye-like process can be generated in loss spectra as a result of using blocking electrode technique. As discussed in Refs.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…On the other hand, β-modes for both solutions have similar dependences below T g . Simple carbohydrate solutions show a relatively large peak in the dielectric relaxation curve derived from the large dipole moment of the hydroxy group [6][7][8][9][10][11]. As the water content is higher, the dielectric strengths for α-mode and β-mode become larger, indicating that the water molecules are contributed to these relaxation modes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the investigations for the molecular motions have not been so developed compared with other biopolymers, such as proteins, because of their less ordered structures, except fundamental saccharides, such as glucose, sucrose and so on [6][7][8][9][10][11]. Most of polysaccharides exist in biological systems, where the systems contain abundant water molecules as a solvent.…”
Section: Introductionmentioning
confidence: 99%